Qual melhor índice para rastreio da vulnerabilidade funcional de pessoas idosas usuárias da atenção primária à saúde? Análise comparativa entre o VES-13 e o IVCF-20 baseada na classificação internacional de funcionalidade, incapacidade e saúde - Bonifácio, Sandra Regina (2023)
Introduction: The International Classification of Functioning, Disability, and Health (ICF) offers a biopsychosocial model perspective, guiding integrated and humanized clinical practice. Its codes and qualifiers standardize language and can facilitate data collection in health information systems, making it relevant for the care of older individuals in Primary Health Care (PHC). Objective: To compare the content addressed by functional vulnerability indices in older people with the concepts encompassed by the ICF. Methods: Two studies were conducted. In Study 1, we investigated the relationship between the Vulnerable Elders Survey-13 (VES-13) and the Índice de Vulnerabilidade Clínico Funcional-20 (IVCF-20) with the ICF. To achieve this, content analysis was performed through rules of linkage with the ICF, and we also analyzed the convergent validity between VES-13 and IVCF-20 with measures developed from the ICF, such as the World Health Disability Assessment Schedule – Brazilian version for older people (WHODAS 2.0-B.O) and the core set for physical health of older individuals. In Study 2, the aim was to qualify the ICF categories linked to VES-13 through equivalence of the scores of this index with the qualifiers of the ICF. Results: Both indices predominantly assessed the component of activities and participation of the ICF. However, IVCF-20 also encompassed concepts related to body functions and environmental factors. VES-13 exhibited adequate convergent validity, showing more consistent correlations with measures based on the ICF, while IVCF-20 demonstrated weaker correlations with WHODAS 2.0-B.O. The results of Study 2 revealed that the majority of participants were vulnerable older individuals, with specific activities, such as "Shopping for personal items," "Handling money," "Performing light household tasks," and "Taking a shower or bath," being the most severely compromised, classified with a qualifier of 3 (severe problem), while other activities were categorized with qualifiers ranging from 1 (mild limitations) to 2 (moderate limitations). Conclusion: Both indices, VES-13 and IVCF-20, primarily focus on assessing the activities and participation component of the ICF. Nevertheless, VES-13 exhibited a higher degree of convergence with measures developed from the ICF, such as WHODAS 2.0- B.O and the core set, demonstrating adequate convergent validity. The association of activities evaluated by VES-13 with ICF qualifiers provided a comprehensive understanding of functionality in older individuals, revealing a range of degrees of limitations in activities, going beyond the categorical approach found in some items of VES-13. This has significant implications for geriatric care, emphasizing the importance of specific interventions and personalized support.